Savings And Investment Behaviour Of Rubber Cultivators-A Micro Level Analysis - Abhilash T Gopal (Department of Rural Banking and Finance Management, College of Co-operation Banking and Management, 1998)
The study entitled ‘Savings and Investment Behaviour of Rubber Cultivators- A Micro Level Analysis’ was conducted with the following objectives. To analyse the extent and pattern of savings and investment of rubber cultivators. To examine the factors influencing their savings and investment decisions. The study was confined to the rubber cultivators in Meenachil taluk of Kottayam district. The study period was Sep.1996 to Aug. 1997. The sample frame comprised 150 respondents and the respondents were classified into three groups based on their size of holdings. The groups are S1-below 1 hectare (ha), S2 between 1ha and 2ha and S3 between 2ha and 5 ha. The data collected from 150 respondents were tabulated and analysed. The study revealed that the extent of savings was highest for group S3 followed by group S1 and S2. The results indicate that the cultivation of rubber was the major source of income (almost 75 per cent of total income) in all the three cultivator groups considered for the study. Hence the size of rubber cultivation was the major income side determinant of extent of savings among the sample households. However the rate of savings showed a different pattern. The average propensity to save is lowest in group S2 (23 per cent) and is highest in group S3 (36 per cent) closely followed by group S1 (34 per cent). Though the total amount of expenditure is highest in groupS3, its extent and rate of savings are highest as it has managed a very high amount of net income. Despite having the lowest extent of net income the group S1 has achieved an appreciable rate of savings by controlling their total expenditure. From the responses of the cultivators five items viz. education of the children, ceremonies, putting up houses, saving for emergencies and bequeathing assets to spouses and children were emerged as the principal motivations for saving. The savings was mainly disposed in the form of investments in financial assets. The other major form of disposition of savings was investments in nonincome generating assets like household durables and buildings. Among the financial assets bank deposit was the most preferred option of the respondents and co-operative bank deposits had an edge over others. Rate of return followed by safety and proximity were emerged as major parameters influencing the investment options in financial assets. Investment in non income generating assets was found increasing with the increase in the size of holding. Their personal use apart, status concern and demonstration effect were the prime motivations behind such investment. The study established that though the savings is mainly generated from agriculture sector, (especially from rubber cultivation) such savings are not appropriately ploughed as investment in the same sector. Instead the savings is mainly disposed either as financial assets (a low risk low return option) or as unproductive investments.